Konsep ibu dan anak dalam al qur’an dan hadis - Suwito, Komariah; Yahiji, Kasim; Husain, Rahmin Thalib; Daud, Ilyas (Lebah, 2024)
The concept of the relationship between mother and child is found in the Koran and Hadith, which are the two main sources of teaching in Islam. The Koran and Hadith describe the relationship between mother and child as one full of affection, sacrifice and continuity of offspring. This understanding provides a moral basis for forming a family that is harmonious and full of religious values. Mothers have the right to be respected and well cared for, while children have the obligation to be filial, respect and care for their mothers. It is hoped that a deep understanding of this balance will be able to create healthy relationships within the family. The application of the values of love, respect and helping each other is expected to be able to form a family environment that reflects Islamic teachings. So that it is able to provide a holistic view of the concept of mother and child in Islam and its relevance in forming a moral and harmonious society